2015
DOI: 10.1002/lsm.22371
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ti:sapphire laser on shear bond strength of orthodontic brackets to ceramic surfaces

Abstract: Within the limitations of this in vitro study, Ti:sapphire laser- treated surfaces had the highest SBS values. Therefore, this technique may be useful for the pretreatment of ceramic surfaces as an alternative to 'conventional' techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
1
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 35 publications
3
31
1
3
Order By: Relevance
“…Kara et al 35 and Dilber et al 38 demonstrated the efficacy of this laser at 10 W power and 20 Hz frequency for surface etching; the results showed the same level of surface modification as HF. Erdur et al 23 used Er:YAG with an output power of 1-6 W and frequency of 20 Hz and reported non-acceptable SBS; the surface roughness evaluated by electronic microscope was not acceptable as well. While in this study Er:YAG was not beneficial, titanium sapphire laser could deliver efficient changes at 0.45 W power.…”
Section: Resultsmentioning
confidence: 99%
“…Kara et al 35 and Dilber et al 38 demonstrated the efficacy of this laser at 10 W power and 20 Hz frequency for surface etching; the results showed the same level of surface modification as HF. Erdur et al 23 used Er:YAG with an output power of 1-6 W and frequency of 20 Hz and reported non-acceptable SBS; the surface roughness evaluated by electronic microscope was not acceptable as well. While in this study Er:YAG was not beneficial, titanium sapphire laser could deliver efficient changes at 0.45 W power.…”
Section: Resultsmentioning
confidence: 99%
“…Zirconia flat plates were used so the shape and dimensions of the adherent surfaces could be standardized through the experiment, being reproducible, and so the results could be compared to similar researches [ 12 , 13 , 15 ]. Square shape was chosen rather than round since it was found to be more stable in the acrylic resin bases during testing.…”
Section: Discussionmentioning
confidence: 99%
“…SBS tests were conducted according to the standards used in the last published studies on bracket-to-ceramic adhesion [ 12 , 13 , 17 , 18 ]. All bonded specimens were mounted perpendicularly on acrylic resin bases and underwent shear loading using a knife edge system at a crosshead speed of 0.5 mm / min until they fractured, using a universal testing machine (AGS-X Autograph, Shimadzu Corporation, Kyoto, Japan).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations